Le Fort I fracture in a patient victim of a motorcycle accident: case report (Research, Society and Development, 2021)
Case report: Patient F.J.L., male, 51 years old, normosystemic, attended the Maxillofacial Surgery and Traumatology Service of Hospital Batista Memorial, Fortaleza / CE. During the clinical evaluation, mobility of the maxilla, the presence of a step in the zygomatic pillar bilaterally, a step in the infraorbital margin and monocular diplopia in the left eye were verified. After the analysis of the imaging exam, a Le Fort I and zygomatic complex fracture was found, and then the patient underwent surgery under general anesthesia to perform osteosynthesis of the facial fractures, using plates and screws of the 2.0mm and 1.5 system mm. Currently, the patient is in postoperative follow-up for 6 months without functional aesthetic complaints. Conclusion: Early treatment combined with correct planning of maxillofacial fractures significantly minimizes the risks of esthetic-functional impairment, thus favoring the early return of patients to social life and minimizing the risk of postoperative complications.